pH- and Temperature-Dependent Strain Hardening of Sodium Caseinate Gels (Annual Transactions of the Nordic Rheology Society, 2024)
Sodium caseinate, a protein ingredient produced from the major protein fraction in bovine milk, can form acid-induced gels that show interesting strain hardening behaviour in large oscillation amplitude shear. For the first time it was investigated whether the strain hardening of sodium caseinate gels depends on the time point at which the strain sweep is conducted. For this purpose, strain sweeps were started at various time points during the acidification, and the G’ values were related to those obtained in small amplitude oscillatory shear (SAOS) experiments at the same time. The results showed that the strain hardening behaviour is in fact not constant during the gelation process. Interestingly, the smallest overshoot factor was observed around the maximum G’ in SAOS experiments, whereas it increased again with the pH further decreasing.